PENGARUH NAUNGAN DAN PEMUPUKAN NITROGEN TERHADAP KARAKTERISTIK MORFOLOGIS RUMPUT GAJAH DWARF (Pennisetum purpureum cv Mott) - Rellam, Charel Rily; Anis, S.; Rumambi, A.; ., Rustandi (Universitas Sam Ratulangi, 2017)
THE EFFECT OF SHADING AND NITROGEN FERTILIZATION ON MORPHOLOGICAL CHARACTERISTICS OF DWARF ELEPHANT GRASS (Pennisetum purpureum cv. mott). This study was conducted to determine the responses of Dwarf Elephant grass (P. purpureum cv. Mott.) fertilized with different nitrogen levels and at different shading areas. A Completely Randomized Design (CRD) in a Factorial arrangement with 2 factors of nitrogen levels and shading areas arranged as follows: factor A = fertilization levels of P1 = without fertilization (0%); P2 = 200 kg urea/ha; P3 = 400 kg urea/ha; and P4 = 800 kg urea/ha; whereas factor B = shasing areas of N1 = no shading area (0%), and N2 = 70% shading area. Variables measured were including leaf length, number of mature leaves, and plant height. Research results showed that plants needed about 200 kg urea/ha in order to achieve maximum leaf length in shaded area; whereas plants within no shading area needed about 800 kg urea/ha to achieve maximum leaf length. To achieve maximum number of mature leaves in open area without shading plants needed about 800 kg urea/ha, and no need for nitrogen fertilization in shading area for plants to achieve such a maximum number of mature leaves. The highest plant height was achieved at the level of 400 kg urea/ha fertilization at open area (no shading), and there was no need of nitrogen fertilization for plants in shaded area in order to achieve their maximum height. It can be concluded that shading positively contributed to the availability of nitrogen to be used by Dwarf Elephant grass (P. purpureum cv. Mott.). In open area without shading, plants need more nitrogen in the form of urea to produce leaf length, number of mature leaves, and plant height compared to shaded area.Keywords: Fertilization, Shading, Elephant Grass, Plant morphology.